Sikap Etis Hamba Tuhan Terhadap Panggilan Allah dan Tugas Pelayanan Berdasarkan Filipi 2:21-22 - Georges Nicolas Djone; Martin Luther Manao; Martin Laia; Timothy Amien Rk; Soneta Sang Surya Siahaan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This writing aims to analyze what should be the attitude of God's servants ethically towards God's call and service tasks that God has entrusted to him based on Philippians 2:21-21. God's call is God's initiative and will in His grace for everyone He has chosen, and the service that God has entrusted to His servants is an honor. However, it was found that some of God's servants did not show an ethical attitude in accordance with their status as God's servants, so that they became a stumbling block within the church environment as a community of believers, as well as outside the church as an environment to be reached for Christ. In this paper, the approach used is descriptive qualitative method, by collecting data through the Bible and other literature books such as journals, interviews and as well as through documents that have a relationship with the topic of discussion such as social media Youtube. As a result, a servant of God is ethically obliged to have the nature of loyalty to God who has called him. Second, a servant of God is ethically obligated to be an example in the service that God has entrusted to him. In conclusion, a servant of God is essentially an ethical human being because he is called by God who is the Source of Ethics, so that the servant of God needs to clearly grasp the essence of his calling by realizing that serving is an honor and grace in God's call. Thus he is required to show an ethical attitude, namely: a servant of God is ethically obliged to have the nature of loyalty to God who has called him. Second, a servant of God is ethically obligated to be an example in the service that God has entrusted to him.